Analysis of outcome of vaginal hysterectomy and pelvic floor repair by POPQ system - Devnikar, Komal; Palve, Tushar; Shaikh, Soheil; Bulchandani, Priya; Kulkarni, Sejal; Thatikonda, Rajashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To assess the relief of symptoms and efficacy of vaginal hysterectomy and pelvic floor repair surgeries in patients with pelvic organ prolapse. Methods: A total of 55 women participated in the study. Vaginal hysterectomy with or without anterior and posterior colporrhaphy and fothergills surgery were done in all cases. Patients were followed postoperatively about symptom relief and the anatomical correction was analyzed at 6 months using Pelvic Organ Prolapse-Quantification (POP-Q) System. Results: The highest incidence of POP was between 41 to 50 years of age and in multiparous women with parity 2 and more than 4. 36.36% had stage III prolapse when measured using the POPQ classification. Something coming out per vaginum was the commonest complaint seen in 100% of the patients. The improvement of all symptoms was significant (p value <0.05). Conclusions: There is significant anatomical restoration and symptom relief after surgery by POPQ.